Implementasi Pembinaan dan Pengawasan Waralaba di Bimbingan Belajar Primagama Kota Batam - Ayunda, Rahmi (Universitas Internasional Batam, 2019)
This researcg discusses the effectiveness of the development and supervision of franchises in Batam city. The formulation of the problem in this thesis is related to the effectiveness of article 14 and article 15 in the community, problems in the application of article 14 and article 15 as well as solutions in dealing with problems in the application of article 14 and article 15. This research is included in the category of juridical-sociological research which in the method of conducting research is by examining secondary data first, then proceed with conducting research on primary data in the field by conducting interviews. Data were processed and analyzed using qualitative methods and conclusions were drawn descriptively. Testing the effectiveness of the application of article 14 and article 15 of Government Regulation No. 42 of 2007 was carried out using the theory of legal effectiveness proposed by Soerjono Soekanto. From the effectiveness test using the theory, it was concluded that Article 14 and Article 15 have not been optimally and effectively implemented. Law Enforcement Factors are the main factors of the ineffectiveness of the implementation of Article 14 and Article 15. The Department of Industry and Trade and Energy of Mineral Resources in Batam City has never even provided guidance or supervision on tuition course in Batam city. The need to develop derivative rules in the form of Mayor Regulations becomes a recommendation in dealing with the problems discussed in this research.